HEALTH, SAFETY, AND ENVIRONMENTAL CHALLENGES IN CRUDE OIL TRANSPORT: LESSONS FROM THE EXXON VALDEZ SPILL - C. Emetumah, Faisal; N. Duru, Patricia (African Journal of Social and Behavioural Sciences, 2025)
Workplace accidents, especially in high-risk work environments, are inevitable at times. However, inadequate attention to health, safety, and environmental management (HSEM) in the workplace can lead to accidents that can significantly harm humans and the natural environment. The study examined Health, Safety and Environmental complexities resulting from the 1989 Exxon Valdez oil spill (EVOS) shipping accident in Alaska. The methodology adopted for the study involved secondary data collection using an exploratory approach. Study results show that EVOS led to serious environmental degradation and also caused significant sociocultural, psychological, economic and health impacts. The main complexity and interaction of HSEM resulting from EVOS is the dilemma of balancing HSE goals with economic goals. Even though the prevalence of shipping tanker accidents resulting in oil spills has significantly reduced, accidents attributable to human inadequacies still occur. Also, post-traumatic stress disorders caused by the social, economic and environmental effects of EVOS are still felt in the areas affected. In addition, the remediation techniques applied have not been very effective in mitigating the spill’s environmental effects despite repeated applications. Therefore, the study recommends that International Oil Companies (IOCs) should strive to maintain a balance between economic and HSEM goals, thereby fostering sustainability in the shipping sector.